Effects of Indomethacin on the Norepinephrine-Induced Contraction in Vascular Smooth Muscle During Different Stages of the Estrous Cycle - Laurido-Fuenzalida, C; Martinez-Salinas, J; Morales-Munoz, B; Jaimes-Fernandez, L (University of Agriculture, 2019)
Previous studies have shown that vascular reactivity evaluated in female rat aorta to norepinephrine did not present the same response at all periods of their estrous cycle. During proestrus, the contractile response shows lower values. It was also reported that vascular reactivity had a close relationship with prostaglandins activity. In this study, we studied the response to norepinephrine in rat aorta rings treated with indomethacin. Indomethacin is a well-known inhibitor of prostaglandin synthesis. At low concentrations, the effect of indomethacin was not significant, and vascular reactivity response to norepinephrine was similar to those aortic rings from the control rats (without indomethacin). However, at high concentrations of norepinephrine, a marked difference was observed. The inhibitory action of indomethacin on the synthesis of prostaglandins was effectively reflected in a lower release of prostaglandins. In this way, our results confirm previous findings and indicate that indomethacin increases the constrictor response to norepinephrine, avoiding the vasodilatory effect of prostaglandins. © 2019 University of Agriculture. All rights reserved.
Keywords: Norepinephrine; Prostaglandins; Rat aorta; Vascular reactivity